Medical applications of liposomes - Lasic, D. D.; Papahadjopoulos, Demetrios (Elsevier, 1998)
The development of liposomes as a drug delivery system has fluctuated since its introduction in the late 1960's by A.D. Bangham. While academic research of liposomes as a model membrane system has always flourished, as the exponential growth of papers can testify, the application of these findings to medically useful products has gone through several crises. Following the original optimism in the 70's and early 80's, a period of severe skepticism ensued at the end of the 80's and beginning of the 90's, culminating in a moderate but real optimism in the mid 90's, as a result of a successful launch of the first products in the US and Europe. In this collection of papers, the editors have gathered the most promising ideas, approaches, applications and commercial developments, thereby presenting an up-to-date compilation of the present status of the field. This includes such broad areas as anti-cancer chemotherapy immune stimulation and infectious diseases. Currently, the major areas of progress are in delivery of anti-fungal agents by conventional liposomes or lipid-based carriers and systemic anticancer therapy using long-circulating liposomes. The future applications as characterized by the direction of present day research is in specific targeting and delivery of informational molecules such as DNA plasmids (genes), antisense oligonucleotides or ribozymes. Other future developments may be in topical delivery, vaccination and in diagnostics. Features of this book: & bull; Contributions from almost all the leading labs in the field & bull; Up-to-date, critical reviews bridged by editors' introductions & bull; Organized into a logical framework.